La linea Pirandello–Shaw in base alla critica - Szabados, Edina (Verbum – Analecta Neolatina, 2011)
In this paper, I discuss the possible parallels suggested by various critics between the dramatic art of Luigi Pirandello and that of G. B. Shaw. Only few critics, such as Walter Starkie and Eric Bentley, dealt with this question thoroughly. Starkie states that there are not many similarities between the works of the two artists. In order to support this statement, he studied the main characteristics of the Pirandellian and the Shavian plays, observed the stage directions, and the heroes and heroines represented in the dramas. After this, I study Bentley's views on the intellectualism of Pirandello and Shaw, and how they react to the question of illusion and reality as an everyday experience. The summary of the Pirandello-Shaw criticism provides a basis for my further studies of these arguments.